Use of monoclonal antibodies to probe subunit- and polymer-specific epitopes of 987P fimbriae of Escherichia coli. - Schifferli, D M (1987)
The relationship between the structure and biological function of 987P fimbriae of a strain of enterotoxigenic Escherichia coli (O9:K103:H-) from piglets was investigated. A set of four monoclonal antibodies was prepared from the spleen cells of mice immunized with isolated 987P fimbriae. Antibodies E11, D5, and C3, but not G10, reacted in enzyme-linked immunosorbent assays with 987P fimbriae-bearing E. coli. Electron microscopy showed that E11 and D5 reacted in a discrete periodic pattern forming a spiral motif along the length of the fimbriae. The results of enzyme-linked immunosorbent assays were in agreement with these results; antibodies E11 and D5 reacted at a high dilution (1:12,000) with native fimbriae on the surface of E. coli, whereas antibody C3 reacted at an intermediate dilution (1:3,000) and G10 failed to react at all (less than 1:250). In contrast, C3 and G10 reacted at a dilution of 1:3,276,000 with the fimbrial subunits derived by treating the isolated fimbriae with 6 M guanidine hydrochloride, whereas E11 and D5 reacted with the subunits at much lower dilutions of 1:800 and 1:6,400, respectively. Moreover, fimbriae reassembled from the subunits regained reactivity with antibodies D5 and E11, indicating that these antibodies are directed against quaternary conformational epitopes. Only the three antibodies (D5, E11, and C3) that recognized epitopes accessible on intact fimbriae were able to efficiently block the adhesion of 987P fimbriated E. coli to piglet enterocytes. These results indicate that certain epitopes of 987P fimbriae are dependent on quaternary structural conformation, whereas others are present on monomeric subunits; some of the latter appear to remain accessible on fully assembled fimbriae.